2002
DOI: 10.1016/s1535-6108(02)00215-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic unmasking of epigenetically silenced tumor suppressor genes in esophageal squamous cell carcinoma

Abstract: We performed a comprehensive survey of commonly inactivated tumor suppressor genes in esophageal squamous cell carcinoma (ESCC) based on functional reactivation of epigenetically silenced tumor suppressor genes by 5-aza-2'-deoxycytidine and trichostatin A using microarrays containing 12599 genes. Among 58 genes identified by this approach, 44 (76%) harbored dense CpG islands in the promoter regions. Thirteen of twenty-two tested gene promoters were methylated in cell lines, and ten in primary ESCC accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
297
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 301 publications
(317 citation statements)
references
References 53 publications
14
297
1
2
Order By: Relevance
“…We extracted genomic DNA and carried out bisulphite modification of genomic DNA as described previously (Yamashita et al, 2002). Briefly, 2 mg of DNA in 20 ml of H 2 O containing 5 mg of salmon sperm DNA were denatured by incubation with 0.3 M NaOH at 501C for 20 min.…”
Section: Bisulphite Treatmentmentioning
confidence: 99%
“…We extracted genomic DNA and carried out bisulphite modification of genomic DNA as described previously (Yamashita et al, 2002). Briefly, 2 mg of DNA in 20 ml of H 2 O containing 5 mg of salmon sperm DNA were denatured by incubation with 0.3 M NaOH at 501C for 20 min.…”
Section: Bisulphite Treatmentmentioning
confidence: 99%
“…Initially, significant progress was made by functional epigenomic approaches using gene expression microarrays to study changes in gene expression following global demethylation of cancer cell line genomes (Yamashita et al, 2002;Sato et al, 2003;Lodygin et al, 2005). For RCC, this approach resulted in the identification of B14 candidate RCC TSGs (Morris et al, 2005(Morris et al, , 2010Ibanez de Caceres et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Of these modifications, acetylation is controlled by histone acetyltransferases and histone deacetylases (HDACs) which control gene expression by remodeling the nucleosomes leading to either transcriptional activation or repression, respectively (Kondo et al, 2004). Two chemical agents commonly used to modulate the expression of silenced genes in cancer cells are 5-aza-2 0 -deoxycytitdine (5-aza-dC), which is an inhibitor of DNA methylation and trichostatin A (TSA), an inhibitor of histone deacetylation (Marks et al, 2001;Johnstone, 2002;Yamashita et al, 2002). Gene expression studies revealed that the effects of 5-aza-dC are similar to those of TSA exposure than either of the somatic cell DNA methyltransferase knockouts (DNMT knockouts), implying a converging mechanism for these agents (Gius et al, 2004).…”
Section: Introductionmentioning
confidence: 99%